Emergence of ON1 genotype of human respiratory syncytial virus subgroup A in China between 2011 and 2015 - Jinhua Song; Yan Zhang; Huiling Wang; Jing Shi; Liwei Sun; Xiaojie Zhang; Zifeng Yang; Wenda Guan; Hong Zhang; Pengbo Yu; Zhengde Xie; Aili Cui; et al. (Scientific Reports, 2017)
Abstract A molecular epidemiological study of human respiratory syncytial virus (HRSV) was conducted to examine the distribution of its subgroups and genotypes, as well as to identify its transmission pattern in China. A total of 705 samples collected from 9 provinces in China between January 2008 and February 2015 were identified as HRSV-positive and were subsequently sequenced. Of these, 336 samples were HRSV subgroup A (HRSVA), 368 samples were HRSV subgroup B (HRSVB), and 1 sample contained both HRSVA and HRSVB. These 705 HRSV sequences, together with 766 HRSV sequences downloaded from GenBank, were analyzed to understand the recent circulation patterns of HRSV in China. HRSVB predominated in the 2008/2009 and 2009/2010 seasons, whereas HRSVA predominated in the 2010/2011 and 2011/2012 seasons; HRSVA and HRSVB co-circulated during 2012/2013 and 2014/2015. Phylogenetic analysis showed most of the HRSVA sequences clustered into 2 genotypes, namely, NA1 and ON1. The ON1 genotype was first detected in China in 2011, and it quickly replaced the NA1 genotype to become the most prevalent HRSVA genotype circulating in China between 2013 and 2015. Continuous epidemiological surveillance and molecular characterization of HRSV should be conducted to monitor the evolution of HRSV in China.